STUDENTS’ RESPONSES TOWARDS THE USE OF LANGUAGE INSTRUCTIONS BY LECTURERS IN EAP CLASSROOMS - Amanda Pradhani Yanwar (Universitas Islam Negeri Alauddin Makassar, 2020)
This research was aimed to describe the students’ responses toward the use of language instructions. It was conducted at Unit Pelaksana Teknis Bahasa, Universitas Sebelas Maret, Surakarta, Indonesia. The techniques for collecting the data used in this research were observation, interview, document analysis, and questionnaire. Based on the analysis of the data, it can be concluded that the students could interact with the lecturer when the lecturer used both English and Indonesian language during the teaching and learning process. Therefore, it is recommended for English lecturers to use language instructions properly to make the students understand more about what the lecturer is talking about, to make the students accustomed more about the use of English vocabularies, to make the lecturers and the students have an enjoyable and successful English teaching and learning process. For the other researchers who want to conduct similar research, the result of this research can be an additional reference.